Conservation prototype grants management and planning system. Volume 7 of the sourcebook (Department of Energy, Washington, D.C. (USA). Office of Conservation and Solar Applications, 1978)
Part C, Title III, of Public Law 94-163, the Energy Policy and Conservation Act of 1975 established a program for State Energy Conservation Plans designed to promote the conservation of energy and reduce the rate of energy demand growth. The Act authorized the Federal Energy Administration, which since has become part of the Department of Energy, to establish procedures for the program and to grant financial and technical assistance to eligible States in support of their Energy Conservation Plans. This manual describes a prototype Grant Management and Planning System (GMPS) which the States may adopt on a voluntary basis to administer grants under the Act. The system has been developed as a national prototype under the auspices of the Office of Conservation and Energy Resource Development, Region I, Boston, Massachusetts. The basic objective of the system is to provide pertinent financial and performance information for effective management of State Energy Conservation Programs. The program management concepts used in GMPS were derived from the ERDA-Uniform Contractor Reporting Guidelines which provided a foundation adaptable to the unique elements of the various State financial and reporting systems.